1988
DOI: 10.1002/ar.1092210310
|View full text |Cite
|
Sign up to set email alerts
|

Intra and juxtavagal paraganglia: A topographical, histochemical, and ultrastructural study in the human

Abstract: The topographical, ultrastructural, and histochemical features of 23 human vagal paraganglia were analyzed. Nineteen of the 23 paraganglia were found in previously unreported sites; 18 of the 19 were in the cervical part of the nerve, between the carotid bifurcation and the superior thoraco-cervical inlet, and one paraganglion was located in the retrothyroidal part of the left inferior laryngeal nerve. The results of ultrastructural studies (2 cases), the histochemical and formaldehyde-induced-fluorescence stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…If a similar distribution applies to humans as well, this could carry implications and their presence should be investigated. The neurons identified by Plenat and colleagues described as "displaced sensory neurons" (Plenat et al, 1988) are most likely the same structures as the vagal extraganglionic neurons described in our current study. There is currently strong interest in the use of vagus nerve stimulation (VNS) as a method to treat depression, epilepsy, and inflammatory diseases (Bonaz et al, 2019; Chavan F I G U R E 8 Direct administration of FG to the stomach wall labels extraganglionic neurons in Wild-type mice.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…If a similar distribution applies to humans as well, this could carry implications and their presence should be investigated. The neurons identified by Plenat and colleagues described as "displaced sensory neurons" (Plenat et al, 1988) are most likely the same structures as the vagal extraganglionic neurons described in our current study. There is currently strong interest in the use of vagus nerve stimulation (VNS) as a method to treat depression, epilepsy, and inflammatory diseases (Bonaz et al, 2019; Chavan F I G U R E 8 Direct administration of FG to the stomach wall labels extraganglionic neurons in Wild-type mice.…”
Section: Discussionsupporting
confidence: 74%
“…Previous findings reported in most textbooks and review articles state that afferent neuronal somas of the mammalian vagus nerve are located in the nodose and jugular ganglia (NG and JG, respectively) (Berthoud & Neuhuber, 2000 ; Li & Schild, 2002 ; Mazzone & Undem, 2016 ; Niu et al, 2020 ; Prescott & Liberles, 2022 ; Zhao et al, 2022 ). However, early anatomical studies described a population of cells that resemble neurons in the histological preparations of vagus nerve tissue from cats, dogs, humans, and newly hatched chicks (Plenat et al, 1988 ). In their 1988 study, Plenat and colleagues (Plenat et al, 1988 ) confirmed the existence of human cells that were “…indistinguishable in shape and histochemical properties from those constituting the inferior vagal ganglion and which were scattered along the trunk or formed microscopic ganglia”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Both the superior and nodose vagal ganglia are proximal to the pars venosa of the jugular foramen, cranial nerves IX to XII, and the ascending portion of the petrous internal carotid artery. 15 Therefore, vagal paragangliomas have distinct therapeutic sequela based on their close anatomical association with the superior portion of the vagal nerve and other adjacent neurovascular structures. [1][2][3] Extra-adrenal paraganglia lack methyltransferase, a requirement for converting norepinephrine to epinephrine; the metabolic breakdown of catecholamines to metanephrine (from epinephrine) and normetanephrine (from norepinephrine) as well as vanillylmandelic acid can be detected in urine.…”
Section: Anatomy and Physiologymentioning
confidence: 99%
“…A constant, however, was the plethora of fine studies that appeared in The Anatomical Record . These include: Lin et al’s () study of pathways communicating with the pterygopalatine ganglion in the cat; Plenat et al's () examination of the intra and juxtavagal paraganglia in humans; Mu and Sanders' () insightful study on the hypoglossal nerve and neuromuscular organization of the tongue in canids; the study by Henry et al () on trigeminal distribution and function in the extraordinary, naked mole rat; George and Holliday's () biting study illuminating alligator trigeminal nerve facial sensation (recommended reading for anyone thinking of moving to Florida); Diaz et al's () insightful overview of the parts of the olfactory system sensu lato ; a thought‐provoking paper by Smith et al () on the vomeronasal organ and its involvement with the olfactory nerve in nonhuman primates (Tim Smith, of Slippery Rock University in Pennsylvania, is recognized as one of the brightest and most creative thinkers in evolutionary morphology today and, fortunately for The Anatomical Record , is also our Associate Editor); and (Boehm and Kondrashov's () insightful study on the distribution of neuron cell bodies in the intraspinal portion of the spinal accessory nerve, to mention but a few.…”
mentioning
confidence: 99%